Skill Formation and the Trouble with Child Non-Cognitive Skill Measures - Emilia Del Bono; Josh Kinsler; Ronni Pavan (Institute of Labor Economics (IZA), 2020)
Research on child skill formation and related policies typically rely on parent- reported measures of child non-cognitive skills. In this paper, we show that parental assessments of child non-cognitive skills are directly affected by the skills of the parents. We develop a dynamic model of child and parental skill formation that accounts for this contamination and show how standard estimates of the production of skills are affected. We then use our model to illustrate how contamination in parental measures of child non-cognitive skills affects estimates of child development policies that also directly affect parental skills.
Keywords: C13; C18; I38; J13; J24; 330; children; human capital; dynamic factor analysis; measurement; policy